Electrocardiographic P wave dispersion may be a risk factor for atrial arrhythmia in the patients with central serous chorioretinopathy - Turgut, Burak; Da?li, Necati; Kobat, Sabiha Güngör; Tanyildizi, Rumeysa; Do?du, Orhan; Kobat, Mehmet (Gazi Eye Foundation, 2017)
Purpose: The aim of this study was to evaluate electrocardiographic P-wave dispersion (PWD) in patients with central serous chorioretinopathy (CSC). Materials and Methods: This comparative, case-control study included 40 patients with CSC at acute phase and 40 age- and sexmatched healthy subjects. The heart rate (HR), P maximum (Pmax), P minimum (Pmin) and PWD were manually measured and analyzed on a 12-lead surface electrocardiograms. Results: There were no significant differences with regard to age, smoking status (rate and duration) and gender among the groups (P>0.05). The participants included 22 men (55%) and 18 women (45%) in the patient group, 20 men (50%) and 20 women (50%) in the control group. The mean Pmax, Pmin, and PWD in the patient group were significantly higher than those of the control group (p=0. 001, p=0. 01 and p=0. 04, respectively). HR did not differ significantly between the study groups (P>0.05). No significant correlation was found between duration of the disorder and PWD values (r= 0.13, P > 0.05). Conclusions: Our study suggests that CSC may be associated with an increased PWD and high risk for atrial arrhythmia. © 2017 Gazi Eye Foundation. All rights reserved.
Keywords: Atrial arrhythmia; Atrial fibrillation; Central serous chorioretinopathy; Electrocardiography; P wave dispersion